2023
DOI: 10.1111/ene.15831
|View full text |Cite
|
Sign up to set email alerts
|

Joint European Academy of Neurology–European Pain Federation–Neuropathic Pain Special Interest Group of the International Association for the Study of Pain guidelines on neuropathic pain assessment

Abstract: Background and Purpose: In these guidelines, we aimed to develop evidence-based recommendations for the use of screening questionnaires and diagnostic tests in patients with neuropathic pain (NeP). Methods:We systematically reviewed studies providing information on the sensitivity and specificity of screening questionnaires, and quantitative sensory testing, neurophysiology, skin biopsy, and corneal confocal microscopy. We also analysed how functional neuroimaging, peripheral nerve blocks, and genetic testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 100 publications
2
9
0
Order By: Relevance
“…Genetic testing targeting peripheral ion channel and transient receptor potential (TRP) genes has recently shown promise in the evaluation of painful neuropathies, 33–35 but is not widely available. There are limited rapid and objective measures of early neurodegeneration 36,37 and DPN may be undiagnosed in 35%–99.8% of patients in Saudi Arabia, 18,22 Qatar, 18,19,38 Kuwait, 18 Germany, 39 United Kingdom, 40 USA, 41,42 Japan, 43 Malaysia, 44 Hong Kong, Philippines, Taiwan and Thailand 45 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic testing targeting peripheral ion channel and transient receptor potential (TRP) genes has recently shown promise in the evaluation of painful neuropathies, 33–35 but is not widely available. There are limited rapid and objective measures of early neurodegeneration 36,37 and DPN may be undiagnosed in 35%–99.8% of patients in Saudi Arabia, 18,22 Qatar, 18,19,38 Kuwait, 18 Germany, 39 United Kingdom, 40 USA, 41,42 Japan, 43 Malaysia, 44 Hong Kong, Philippines, Taiwan and Thailand 45 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is that we did not use standardized questionnaires for neuropathic pain. A recently published guideline on assessment of neuropathic pain using the GRADE system showed that only three of the many questionnaires in use are highly recommended, while IENFD is the only diagnostic method that reaches the same level ( 10 ). Other possible symptoms and findings of small fiber neuropathy such as change of swelling, orthostatism and other autonomic signs were not explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These fibers may be tested by the semi-objective method of quantitative sensory testing (QST), while the gold standard is skin biopsy for quantification of intraepidermal nerve fiber density (IENFD) ( 9 ). Indeed, a recent review on diagnosis of neuropathic pain using the GRADE system found that skin biopsy is so far the only investigation to confirm peripheral neuropathic pain ( 10 ). To our knowledge, this has not previously been performed in patients with DM1.…”
Section: Introductionmentioning
confidence: 99%
“…In the original trial from which these prospective data were taken, pain was not the major study endpoint and the 6-week duration of follow-up was limited. It was also not possible to differentiate between nociceptive and neuropathic pain, chronic versus acute relapse pain, or to identify pain syndromes that occur commonly in MS [ 6 , 27 , 28 ]. The patients were asked to estimate their pain over the preceding 4 weeks at each study visit, introducing the possibility of recall bias.…”
Section: Discussionmentioning
confidence: 99%